FLAVONOID LEVEL TEST ON ETHANOL EXTRACT OF BINJAI LEAF (Mangifera Caesia) (Research report) - Ana Azizah Ansari; Irham Taufiqurrahman; Nurdiana Dewi (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Binjai (Mangifera caesia) is a typical plant from South Kalimantan containing secondary metabolites such as flavonoids. Flavonoids possess antioxidant and anti-inflammatory effects that play an important role in wound healing process. Flavonoid compounds isolation from plants can be affected by many factors, one of which is the concentration of solvents. Therefore, determining solvent concentration that can optimally dissolve flavonoids is important. Purpose: The aim of this research was to discover ethanol solvent concentration that can dissolve flavonoid in Binjai leaf optimally. Methods: This study used a true experimental method with posttest-only control group design, using simple random sampling technique, consisting of seven treatment groups which are treatment group P1, P2, P3, P4, P5 and P6 using ethanol concentration of 50%, 60% , 70%, 80%, 90% and 95%, as well as a control group using n-hexane 95% in the process of maceration. Total flavonoids level is calculated using UV-Vis Spectrophotometer.  Results:  Average levels of total flavonoids contained in group P1, P2, P3, P4, P5, P6 and K were 0,025 mg; 0.055 mg; 0.112 mg; 0.068 mg; 0,049 mg; 0,139 mg and 0,026 mg respectively. One way ANOVA test showed significant differences in each group. Post Hoc LSD test revealed that there was no significant difference between 50% ethanol extract groups with 95% n-hexane extract group, whereas the other groups showed significance. Conclusion: The optimal solvent concentration to dissolve flavonoid in Binjai leaf is 95% of ethanol solvents.